Low Birth Weight and its Relationship with Anemia during Third Trimester among Females - Madiha Fatima, Sumaira Nadeem, Samia Rafique, Ayesha Abdul Sattar, Aneela Nadeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Low birth weight (LBW) is a major problem in different societies especially developing countries. Aim: To compare the frequency of anemia during third trimester among females with low and normal birth weight. Study design: Descriptive cross sectional. Methodology: Study conducted at Department of Obstetrics and Gynaecology, Jinnah Hospital, Lahore. Patients (n=160) were enrolled through probability convenient sampling. All babies underwent assessment for birth weight in minimum clothing using weighing machine following standard protocol and procedure and labeled as low or normal birth weight as WHO criteria. Data was evaluated by using SPSS v.24. Chi square was applied with P-value of <0.05 was considered as significant. Quantitative variables were presented as mean±SD while categorical data was presented as percentage. Results: Mean age of participants was 27.1±5.1 years. There were 61 patients (38.1%) with parity ≤ 2 and 99 patients (61.9%) with parity >2. Comparison of frequency of anemia during 3rd trimester among females with low and normal birth weight revealed statistically significant difference (p=0.049*). Keywords: Anemia, Low Birth Babies, Pregnancy and Parity.